MENYEMAI MODERASI BERAGAMA DALAM MENANGKAL RADIKALISME DAN TERORISME DI INDONESIA - Alit Putrawan I Nyoman (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Indonesia is ranked 37th with the highest terrorism cases globally. A series of successive events since the 2000s. Of course it causes a lot of losses, not only material but also the psychological and mental health of people who are worried about the safety of their lives. This study aims to find out how to counteract radicalism and terrorism in Indonesia. The diversity of religions makes people's anxiety about the existence of terrorism even more complex. What is the religion of Islam that is increasingly cornered and has a negative view. However, even so, individuals who have an obligation to protect this country synergize in preventing the growth of radicalism and every global. Assisted by the government which is expected to ensure the realization of a just, prosperous, and prosperous society.